2022
DOI: 10.1002/dev.22353
|View full text |Cite
|
Sign up to set email alerts
|

The effects of postnatal erythropoietin and nano‐erythropoietin on behavioral alterations by mediating K‐Cl co‐transporter 2 in the valproic acid‐induced rat model of autism

Abstract: In this study, based on the excitatory/inhibitory imbalance theory of autism, the time window of GABA switch, the role of K-Cl co-transporter 2 (KCC2) in adjustment GABA switch, and brain permeability to erythropoietin (EPO), the effects of postnatal -EPO and-nano-erythropoietin (NEPO) have been evaluated in the valproic acid (VPA) rat model of autism. The VPA was administered for animal modeling of autism at gestational day (GD) 12.5 (600 mg/kg). Male offsprings were injected with EPO and NEPO in a clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has also been identified as a neuromodulating agent able to regulate mitochondrial function in the hippocampus and affect cognitive outcomes in an animal model, and that EP300 , a transcriptional regulator of EPO, appears on a “high-confidence” list of genes associated with neurodevelopmental disorders [ 41 44 ]. A recent study highlighted a potential role of erythropoietin in improving autistic-like behaviors in rats with the valproate-induced model of autism, associated with the restored expression of K-Cl cotransporter encoded by Slc12a5 [ 45 ]. Another study suggested that an association may exist between high umbilical cord serum EPO levels and an increased risk for severe neurocognitive morbidity in early childhood even after adjusting for the gestational age [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been identified as a neuromodulating agent able to regulate mitochondrial function in the hippocampus and affect cognitive outcomes in an animal model, and that EP300 , a transcriptional regulator of EPO, appears on a “high-confidence” list of genes associated with neurodevelopmental disorders [ 41 44 ]. A recent study highlighted a potential role of erythropoietin in improving autistic-like behaviors in rats with the valproate-induced model of autism, associated with the restored expression of K-Cl cotransporter encoded by Slc12a5 [ 45 ]. Another study suggested that an association may exist between high umbilical cord serum EPO levels and an increased risk for severe neurocognitive morbidity in early childhood even after adjusting for the gestational age [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SI and SPI scores were between -1 and 1; the values closer to 1 indicate that the animal is more social, while the negative scores show that the animal has no sociability or social preference. 17 …”
Section: Methodsmentioning
confidence: 99%
“…It appears that genetic (De Rubeis et al , 2014; Hansen et al , 2015) and environmental (Chiarotti and Venerosi, 2020) factors influence the pathogenesis of ASD. Researchers have found that the maternal use of valproic acid (VPA) during pregnancy increases the risk of autism in humans (Ornoy, 2009) and rodents (Sabzalizadeh et al 2022; Haratizadeh et al 2023).…”
Section: Introductionmentioning
confidence: 99%